A usable past: a contemporary approach to history for the Western profession of arms. Issue 2 (3rd April 2019) - Evans, Michael
ABSTRACT: The most effective way for the Western profession of arms to use history is to disavow the purism and narrow specialisation of today's academia in favour of developing a contemporary approach to the subject. The latter aims to foster a range of applied diagnostic skills that transcend the temporal dimensions of past, present, and future. A contemporary approach to history for military professionals emphasises the use of inter-disciplinary war studies to enhance policy relevance. In any defense and security organisation, history must be usable in the sense of providing cognitive and interpretative skills for probing relationships between possibility and actuality, between experience and expectation, and between singularity and repetition. Using history to examine such dialectical interconnections is particularly valuable when military establishments confront their essential task of analyzing emerging trends in the future of war.